2014
DOI: 10.1377/hlthaff.2013.0816
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status And Readmissions: Evidence From An Urban Teaching Hospital

Abstract: The Centers for Medicare and Medicaid Services (CMS) Hospital Readmissions Reduction Program has focused attention on ways to reduce thirty-day readmissions and on factors affecting readmission risk. Using inpatient data from an urban teaching hospital, we examined how elements of individual characteristics and neighborhood socioeconomic status influenced the likelihood of readmission under a single fixed organizational and staffing structure. Patients living in high-poverty neighborhoods were 24 percent more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
151
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(157 citation statements)
references
References 25 publications
6
151
0
Order By: Relevance
“…25,26 Previously we found that in 2007, that adults living in high poverty neighborhoods had higher preventable hospitalization rates, 27 adding to the literature on neighborhood poverty and poor health outcomes. [28][29][30][31][32] Given that access to high quality primary care has been receiving renewed attention as part of efforts to transform the health care delivery system (e.g., patient centered medical home 33 and advanced primary care 34,35 ), and the presence of place-based initiatives in NYC to improve the overall resiliency of neighborhoods and support the health of individuals have been initiated or will be implemented, 23 we examined preventable hospitalization rates in New York City by neighborhood poverty to determine if a gap between high and low poverty neighborhoods still exists. In addition, with the health insurance expansion components of the 2010 Patient Protection and Affordable Care Act and requirement of coverage for certain clinical preventive services at no cost, we would expect that preventable hospitalizations would decrease after 2014.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Previously we found that in 2007, that adults living in high poverty neighborhoods had higher preventable hospitalization rates, 27 adding to the literature on neighborhood poverty and poor health outcomes. [28][29][30][31][32] Given that access to high quality primary care has been receiving renewed attention as part of efforts to transform the health care delivery system (e.g., patient centered medical home 33 and advanced primary care 34,35 ), and the presence of place-based initiatives in NYC to improve the overall resiliency of neighborhoods and support the health of individuals have been initiated or will be implemented, 23 we examined preventable hospitalization rates in New York City by neighborhood poverty to determine if a gap between high and low poverty neighborhoods still exists. In addition, with the health insurance expansion components of the 2010 Patient Protection and Affordable Care Act and requirement of coverage for certain clinical preventive services at no cost, we would expect that preventable hospitalizations would decrease after 2014.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][10][11][12] In Sweden, HF hospitalisation rates were 45% higher in individuals on low income than those on high income. [10] In the First National Health and Nutrition Examination Survey in the United States, low education was associated with high HF hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on 1,372 HF hospitalisations to Parkland Memorial Hospital, Texas, Amarasingham et al [6] found that patients from the lowest socioeconomic quintile had higher odds of 30-day readmission to any of the 136 hospitals in the area. In a retrospective cohort study, Hu et al [7] found that patients living in highpoverty neighbourhoods were 28 per cent more likely than others to be readmitted within 30 days of discharge. The findings were based on data from a large (802 beds) teaching hospital in Detroit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies strongly link social, behavioral, and community factors with hospital readmissions, even after accounting for possible variability in quality of care in the hospital. [9][10][11] Moreover, their study did not assess what actually happened during the outpatient follow-up appointment or prior to it. If busy primary care providers fail to receive adequate communication about their patient's hospitalization (e.g., medication changes, test results needing follow-up, or needed follow-up procedures), or cannot review sufficiently documented discharge summaries by the time of the follow-up appointment, they likely will be unable to make appropriate evaluation and management decisions.…”
mentioning
confidence: 99%